(untitled) (Journal of Hama University, 2026)
The study was conducted on twelve (12) high-yielding lactating Friesian Holstein cows, weighing between 450 and 600 kg, as well as local breeds aged between 4 and 9 years. These cows had previously experienced prolonged initial recumbency periods ranging from 24 hours to several days. They were located at the Jib Ramleh Cattle Station, across various farms in the Ghab region, and within individual holdings in the Hama Governorate. The cows were divided into two groups:1. Control Group This group included six (6) pregnant cows in advanced gestation stages—approximately 7 to 9 months—based on their insemination dates. All were clinically healthy as confirmed by comprehensive clinical examinations. Blood samples were collected to compare their values with those of the experimental group.2. Experimental Group This group comprised six (6) cows that had experienced recumbency for varying periods—from 12–24 hours to several days postpartum—due to parturient paresis resulting from calcium deficiency. These cows were unable to stand even 24 hours after receiving two consecutive calcium infusion treatments. Despite this, they remained alert and continued consuming food and water.Clinical Examination Findings Results of the clinical examinations indicated that physiological parameters—including body temperature, pulse rate, respiratory rate and pattern, appetite, rumination, mucosal membrane status, and defecation and urination functions—were all within normal ranges.Biochemical Analysis The study also revealed statistically significant differences in blood potassium ion levels in the experimental group compared to the control group. This deficiency is known to impair neural transmission and skeletal muscle polarization, resulting in weakened contraction of the muscular system and reduced cardiac contractility.